Firm Dynamics and Occupational Choice - Michael Koelle (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
I look at the dynamics of firms when investment decisions interact with occupational choice. To model the implications for firm survival and growth, I extend a neoclassical growth model by an endogenous shutdown condition that is driven by the reservation wage in alternative employment. This model is able to generate multiple steady-state equilibria that arise through convexities in the optimal growth path of a firm. I provide empirical evidence consistent with the model predictions using panel data from urban Colombia. I also structurally estimate the model to identify the wage function in a way that is robust to occupational choices being driven by particular wage offers that are observed as subsequent outcomes. The findings are useful for understanding heterogeneous economic decisions of the large number of self-employed small firm owners in developing countries.
Keywords: J24; L26; O10; 330